Construction of a Strong National Identity through the Manifestation of Kebon Ayu Tourism Village (Case Study: in Gerung District, West Lombok Regency, NTB) - Setiawati, Komang Sulis; Risa Afyatin; Elma Valtiana; Wegy Ammarsani; Jayadin; Egy Herianto (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study examines the construction of a strong national identity through the manifestation of Kebon Ayu tourism village. This research has the urgency that the existing local cultural wisdom can build a national identity. The people of Kebon Ayu Tourism Village have their own identity that distinguishes them from other areas. The method used is a qualitative approach with case studies. The data used are primary data and secondary data collected through observation, interviews, and documentation. The data analysis technique is carried out in several steps, namely data reduction, data display, and verification or drawing conclusions. The results of the study show that there is a history of the formation of the Kebon Ayu Tourism Village which is none other than the idea of the Village Head so that the community continues to carry out activities in the midst of a pandemic even though it does not get the consent of the villagers. The form of Kebon Ayu Village's identity in various tourist destination attractions consists of agro-tourism, cultural tourism, and culinary tourism. In developing tourism in Kebon Ayu Village, challenges and support have arisen, these challenges are a consistent attitude to maintain tourism, lack of community understanding, lack of capital and experience as well as the issue of waste and waterways. Meanwhile, the support provided includes active promotions on social media, maximum service from the Village Government, and cooperative relationships with various parties. The existence of Kebon Ayu Village tourism brings benefits from the economic aspects of the community that are getting better and as a place to preserve the local cultural wisdom of Kebon Ayu Village. Therefore, it can be concluded that through tourism Kebon Ayu Village can build the national identity of the Indonesian nation because it presents the existence of a noble culture that is the identity of the Indonesian nation.